Angiogenesis Biomarkers May Be Useful in the Management of Patients With Indeterminate Pulmonary Nodules - Seder, Christopher W.; Kubasiak, John C.; Pithadia, Ravi; Basu, Sanjib; Fhied, Cristina; Tarhoni, Imad; Davila, Edgar; Alnajjar, Hanan; Chmielewski, Gary W.; Warren, William H.; Liptay, Michael J.; Borgia, Jeffrey A. (The Annals of thoracic surgery, 2015)
Low-dose computed tomography (CT) lung cancer screening is known to have a high false positive rate. This study aims to survey biomarkers of angiogenesis for those capable of assigning clinical significance to indeterminate pulmonary nodules detected through CT imaging studies. An institutional database and specimen repository was used to identify 193 patients with stage I non-small cell lung cancer (T1N0M0) and 110 patients with benign solitary pulmonary nodules detected by CT imaging studies. All specimens were evaluated in a blinded manner for 17 biomarkers of angiogenesis using multiplex immunoassays. Biomarker performance was calculated through the Mann-Whitney rank sum U test and a receiver operator characteristic analysis. These data were used to refine our previously reported multi-analyte classification panel, which was then externally validated against an independent patient cohort (n = 80). A total of 303 patients were screened for 17 biomarkers of angiogenesis. Median nodule size was 1.2 cm for benign cases and 1.8 cm for non-small cell lung cancer, whereas median smoking histories were 25 and 40 pack-years, respectively. Differences in serum concentrations of heparin-binding epidermal growth factor (HB-EGF), epidermal growth factor (EGF), vascular (V)EGF-A, VEGF-C, and VEGF-D were strongly significant (p ≤ 0.001) while follistatin, placental growth factor (PLGF), and bone morphogenic protein (BMP)-9 were significant (p ≤ 0.05) between patients with benign and malignant nodules. Our previously reported multi-analyte classification panel was refined to include interleukin (IL)-6, IL-10, IL-1 receptor antagonist (RA), tumor necrosis factor (TNF)-α, insulin-like growth factor binding protein (IGFBP)-5, IGFBP-4, IGF-2, stromal cell-derived factor (SDF)-1(α+β), HB-EGF, and HGF resulting in improved accuracy and a validated negative predictive value of 96.4%. Angiogenesis biomarkers may be useful in discriminating stage I NSCLC from benign pulmonary nodules.